1997
DOI: 10.1177/026921559701100211
|View full text |Cite
|
Sign up to set email alerts
|

Are there gender differences in functional outcome after stroke?

Abstract: Women seem to be functionally more impaired by stroke than men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
42
1
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(51 citation statements)
references
References 19 publications
5
42
1
3
Order By: Relevance
“…A basic question, especially concerning age, is whether the apparent associations are due to ageing itself or secondary to other causes. Regarding sex, previous researchers have generally reported a negative effect of female sex on functional outcome 5, 19, 20, 21, 22, 23, 24, 25, 26, 27. This is seen also in the present study (for details, see11).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…A basic question, especially concerning age, is whether the apparent associations are due to ageing itself or secondary to other causes. Regarding sex, previous researchers have generally reported a negative effect of female sex on functional outcome 5, 19, 20, 21, 22, 23, 24, 25, 26, 27. This is seen also in the present study (for details, see11).…”
Section: Discussionsupporting
confidence: 86%
“…This has been demonstrated universally and it is also a main finding in our study. In addition higher age,3, 5, 8, 9 female sex,5, 19, 21, 22, 23, 24, 25, 26, 27 prior cerebrovascular disease,3, 5, 8 peripheral artery disease,7 arm paresis,5 diabetes,5, 7 fever,5 TOAST‐classification 4, 28 and infarct location,5, 6, 28 among others, have been reported to be negative predictors. The main results in our study thus are consistent with previous findings, emphasising especially stroke severity and prior cerebrovascular disease in addition to age and sex.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 There were 4 studies specifically designed to identify sex differences in PADL with all finding females had worse functional outcomes after stroke. 9,13,21,22 All studies adjusted for age, 2 adjusted for stroke severity, 21,22 and 2 adjusted for vascular risk factors. 13,21 Among studies not designed to examine sex differences, 5 reported that females had worse outcome than males in unadjusted analyses 10 and independent of age, 11,16,23,24 stroke severity, 23,24 prestroke disability, 23 comorbidities, 24 depression, 11 living alone, 11 recurrent stroke, 11 and cognitive impairments.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, although the functional status at admission in female patients was better, there was no difference between genders in terms of FIM gain and FIM efficiency. Nevertheless, there are conflicting results in the literature on gender and its effect on functional improvement (16)(17)(18)(19)(20)25,28). In a study by Hachisuka et al (16), it has been found that although there was no significant difference in terms of motor function in stroke between female and male patients, FIM scores of male patients with stroke tended to be lower than those of female patients with stroke.…”
Section: Discussionmentioning
confidence: 99%